STUDENTS MATHEMATICAL CRITICAL THINKING ABILITY THROUGH THE APPLICATION OF CREATIVE PROBLEM SOLVING MODEL ASSISTED OPEN-ENDED APPROACH - Jumar Jumar; Yoppy Wahyu Purnomo; Viscal Oktari (AKSIOMA: Jurnal Program Studi Pendidikan Matematika, 2023)
This study aims to see the improvement of students' mathematical critical thinking skills by using the Creative Problem Solving (CPS) model with an Open-Ended (OE) approach. This research is motivated by the low ability to find problem solving solutions to problems that cause students' mathematical critical thinking skills to be low. Learning innovation needs to be done, one of which is through the implementation of the CPS model. The Creative Problem Solving (CPS) model emphasizes problem solving skills that must be possessed by students through 4 stages: problem clarification, expression of opinions, evaluation and selection, and implementation. This research is accompanied by an open-ended approach that helps students solve problems in detail. This research uses a type of quasi experiment with a pretest-postest control group design on the volume of cubes and beams. This research was conducted in two classes, namely VA and VB classes with a sample size of 19 students from a total population of 58 students selected randomly. The research instrument used is through essay test items as many as 5 questions. Based on the results of the T test, the value of Sig. 0.000 > ? (0.05) with an average pretest of 47.42 and an average posttest of 86 with an increase of 38.58. This indicates that the CPS model with the OE approach succeeded in improving the mathematical critical thinking skills of fifth grade students.